Silver nanowire-embedded PDMS with high electrical conductivity: nanowires synthesis, composite processing and electrical analysis. (August 2021) - Karimi-Chaleshtori, R.; Nassajpour-Esfahani, A.H.; Saeri, M.R.; Rezai, P.; Doostmohammadi, A.
Abstract: A simple, fast, and ecofriendly polyol method for the synthesis of silver nanowires (AgNWs) with high aspect ratios is presented. Besides, the effects of reaction parameters on the synthesis process, namely reaction temperature, PVP molecular weight, sodium chloride content, as well as solution mixing rate on the morphology and dimensions of silver nanowires, are thoroughly investigated. AgNWs were fully characterized using FE-SEM, TEM, XRD, FT-IR, and UV–Vis analysis and showed an average diameter of 50 nm. Polymer nanocomposites were fabricated through mixing and curing of the AgNWs, PDMS, and curing agents. The prepared nanocomposites were analyzed microscopically, and their electrical conductivity was measured. PDMS containing 25 wt% AgNWs was considered as an optimal composite, mainly because it possessed a combination of flexibility and transparency, accompanied by the high electrical conductivity of 5840.4 S/cm. This composite can be deemed as a potential candidate in lab-on-a-chip and biosensing applications. Highlights: A simple, fast, and ecofriendly polyol method for the synthesis of silver nanowires (AgNWs) is presented. AgNWs with high aspect ratios are synthesized. Silver nanowire-embedded PDMS composite with high electrical conductivity is fabricated.